Polarization on Twitter during the COVID-19 crisis: Caso Aislado and Periodista Digital - Arce García, Sergio (2021)
The announcement of the State of Alarm in Spain in March 2020 brought with it a period of great information intensity in traditional and digital media. The extraordinary nature of the measure, which provided the Government with exceptional measures to confront the Covid-19 pandemic, gave rise to a tremendously polarized scenario. In this context, some webs known for the dissemination of disinformation campaigns and, even, the promotion of ideas closes to the alt-right, were especially active in networks promoting the dissemination of ideological content with the aim of capturing traffic for subsequent monetization through advertising. This work follows the activity around of two of these webs on Twitter, Caso Aislado and Periodista Digital, with the intention of determinate their role in the political polarization. For more than two months, more than 100,000 tweets were captured, stored and studied using R software and various analysis algorithms to determine their social activity, the possible presence or not of bots or automated profiles, the nature of the content and the emotional charge associated with it. There is an intense organized activity around both portals through a high percentage of apparently automated accounts and the support of influencers profiles. Although with differences inherent around each web, it is possible to glimpse an intentional coordination through campaigns that combine content, use of support accounts and automations.